Lembaga Pendidikan dalam Khazanah Klasik: Telaah Proses Sejarah dan Transmisi Ilmu Pengetahuan - Shobahussurur Shobahussurur (Universitas Darussalam Gontor, 2015)
The history of science and its development process in Islam is not a mere message of religious doctrine, but it has really manifested itself in the stages of the history of science. As a historical fact, Islamic sciences have grown and developed by several factors, either it’s directly related to intellectual Muslim development, or to social factors, political and cultural situations which existed at that time. The spirit of science development has been ongoing continuously from one generation to another. Numbers of research, experiment, discovery, and the development of methodology of science are continuously conducted and developed by Muslims. In the history of Islam, scientific work has fluctuated. Starting from the exploration of the roots of science, this article tries to explain the position and the systematization of knowledge in Islamic literatures. This work also proves that the rise and development of science in Islam, cannot be separated from various educational institutional roles, such as maktabah, kuttâb, halaqah, observatories, hospitals and clinics, Dâr al-Hikmah, Dâr al-’Ilm, and madrasah. Therefore, the development of science in the Islamic world is not only beneficial for Muslims, but also for the entire human race. It is proved that even the renaissance in the Western world took many of its success from Islamic civilization since the 14th century AD.